Sauve-Kapandji Remains a Viable Option for Distal Radioulnar Joint Dysfunction. (September 2022) - Munaretto, Nicholas; Aibinder, William; Moran, Steven; Rizzo, Marco
Introduction: Dysfunction of the distal radioulnar joint (DRUJ) can be significantly debilitating. The Sauve-Kapandji (S-K) procedure can be indicated to address multiple etiologies of DRUJ dysfunction. The purpose of this study was to review our institution's results performing the S-K procedure for DRUJ dysfunction in terms of clinical and radiographic outcomes, as well as complications and reoperations. Methods: A retrospective review of S-K procedures performed at 2 institutions between 1998 and 2017 with a minimum of 1-year follow-up was performed. Preoperative and postoperative visual analog scale (VAS) pain, grip strength, and wrist range of motion were reviewed. Radiographs were reviewed for DRUJ healing, carpal translation, and radiocarpal degenerative changes. Results: The cohort included 35 patients. The mean age was 51 years. The mean follow-up was 49.5 months. The postoperative range of motion was unchanged in regard to pronation, supination, and wrist extension. There was a decrease in wrist flexion from 43 degrees to 34 degrees. Successful union was noted in 100% of the wrists. There was 1 case (2.8%) of progressive ulnar translation and 4 major complications (11.3%). Conclusion: The S-K procedure has several theoretical benefits compared to other procedures for DRUJ dysfunction with results of this study demonstrating excellent pain relief, improved postoperative grip strength, retained wrist pronation, supination, and extension, high rate of successful arthrodesis and low rate of major complications. Level of Evidence: Level IV